2007
DOI: 10.1007/bf03325966
|View full text |Cite
|
Sign up to set email alerts
|

Survey of heavy metals in the catfish Synodontis clarias

Abstract: Elevated levels of heavy metals in the catfish Synodontis clarias can be a good indication of pollution of an aquatic ecosystem due to anthropogenic influence. The concentrations of Zn, Cd, Pb, Mn and Ni were determined in Synodontis clarias caught along a section of Taylor Creek and its associated tributaries. Samples were collected bimonthly between July 1999 and June 2000 in five stations. The metals: Zn, Cd, Ni, Pb and Mn were recorded in appreciable quantities, signifying their bioavailability. The levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 4 publications
2
39
0
5
Order By: Relevance
“…On the other hand comparison results with guide lines showed that for water sample Mn, Fe, Pb and Cr were higher in the study area than [23][24][25][26]. This clearly indicates the presence of either natural or anthropogenic sources of Mn, Fe, Pb and Cr to the water body which may affect aquatic organisms.…”
Section: Metals Levels Comparisons Of Present Study With Related Workmentioning
confidence: 76%
“…On the other hand comparison results with guide lines showed that for water sample Mn, Fe, Pb and Cr were higher in the study area than [23][24][25][26]. This clearly indicates the presence of either natural or anthropogenic sources of Mn, Fe, Pb and Cr to the water body which may affect aquatic organisms.…”
Section: Metals Levels Comparisons Of Present Study With Related Workmentioning
confidence: 76%
“…Su concentración promedio en este estudio (Cr = 0,971 µg g -1 ; Ni = 0,572 µg g -1 ) fue inferior (Cr = 80,6-94,5%; Ni = 42,8%) a la establecida en normas internacionales. Ella no excede los valores publicados por otros investigadores (Eisler, 1986;WHO, 1991;Agbozu et al, 2007). Este comportamiento es diferente para valores individuales, donde en algunos casos (Ni = 15,6%) la regulación internacional fue excedida.…”
Section: Discussionunclassified
“…Al momento, la pesquería de bagre en la región se encuentra aprovechada al máximo sostenible sólo en el estado de Tabasco, alcanzando una captura anual aproximada de 4.000 ton (Secretaria de Agricultura, Ganadería, Desarrollo Rural, Pesca y Alimentación, 2004). Contaminantes persistentes, bioacumulables y tóxicos han sido encontrados en otras especies de bagre (Achura & Osakwe, 2003;Adhikari, 2003;Cizdziel et al, 2003;Elia et al, 2003;Shukla et al, 2003;Viljoen et al, 2003;Agbozu et al, 2007). En A. felis su presencia se encuentra poco estudiada.…”
Section: Introductionunclassified
“…Trace metals are ubiquitous in aquatic environments [7]. Some of these metal contaminants are crucial due to their potential toxicity [8] and have potential impact on human health if they reach levels such that they constitute toxic pollutants [9].In addition, metals including Cu, Fe, Mn, and Ni are essential micronutrients for the life processes of animals and plants [10], but imbalances of these metals may be fatal [11]. Furthermore, [12] observed that elements such as As, Pb, Zn, and Cd exhibit extreme toxicity, even at low levels.…”
Section: Introductionmentioning
confidence: 99%